Impact of Team Identification on Fans’ Trust after Negative Incident: Moderating Role of Mass Media - UZMA NOOR; DR. ABDUL QAYYUM; DR. SHAMS UR REHMAN (Journal of Business & Tourism, 2021)
Sports marketing being a new and under researched area is highly dependent on mass media treatment. The purpose of this study is twofold: First to examine the impact of team identification on fans trust after the involvement of a player in a negative incident, and second to examine the impact of media (fans’ perceived content informativeness, content credibility and source credibility of TV cricket talk shows) on this relationship. Data is collected via convenience sampling from a total of 399 respondents belonging to three universities, local markets, and friends from Islamabad and Rawal Pindi twin cities of Pakistan. Simple and moderated multiple regression analysis reveals that team identification positively affects fans’ trust after negative incident. Perceived source credibility, content credibility and informativeness of cricket talk shows on TV (mass media) moderates the relationship of team identification and fans’ trust after negative incident in such a way that the relationship becomes stronger regardless the media is positively or negatively highlighting the negative incident. The results of the current research might help sports marketing and media related organizations to understand sports fans’ behaviors towards sports organizations in connection of the conflict.